Obtención de callos embriogénicos apartir de explantes florales en 2 clones de cacao theobroma cacao l - Valarezo Cueva, Roger Efrain (2015)
In the biotechnology laboratory of the College of Agricultural Sciences at the Universidad Técnica de Machala, research on callus formation in Theobroma cacao from floral explants trying different types of culture media was performed.The objectives wereTo determine which of the two explants studied is most suitable for obtaining individual callus clones.To determine which of the three culture media is most suitable for callus formation.In the study I used cocoa flowers, autoclave, laminar flow chamber, pH meter, precision balance, a fridge, hygrothermograph, bunsen burner, tongs, sodium hypochlorite (NaOCl), carbon source (sucrose and glucose), graduated test tube and volumetric pipettes, funnels, beakers, balls, boxes petrix, glass bottle, erlenmeyer, stirring rod, scalpel, distilled water. The treatments were T1 EET-48 + Base + petal culture medium 1, T2 EET-48 + Base + petal culture medium 2, T3 EET-48 + Base + Culture medium petal 3, T4 EET-48 + base culture medium stamens + 1 T5 EET-48 + base + culture medium stamens 2 T6 EET-48 + base + culture medium stamens 3 T7 EET-103 + base + petal Middle cultivation 1 , T8 EET-103 + Base + petal culture medium 2, T9 EET-103 + Base + culture medium petal 3, T10 EET-103 + Base + Medium cultivo1 stamens, T11 EET-103 + Base stamens culture medium + 2 T12 EET-103 + Base + culture medium stamens 3.The studied variables were, percentage of contamination at 14 days, Size callus formation at 20 days, evolutionary state of callus after 30 days, percentage of callus formation at 45 days.Flower buds were collected unripe from 6-8 in the morning to avoid rear opening, subsequently place them in a bowl with cold water and proceeded to lead the laboratory. The material is then transferred to the laminar flow chamber, the collected buttons were disinfected in the following manner: The buttons were washed with plain water, followed by immersion in sodium hypochlorite (NaOCl) to 25% (v / v) for 10 minutes and three rinses with sterile distilled water.Explants are placed in petri dishes containing 60 mm x 15 7 to 8 ml of semisolid medium PCG (Primary Callus Growth Medium). Each petri dish contained five stamens bases petals 5 bases belonging to the same button, distributed uniformly throughout the surface of the medium, ensuring good contact with the explant culture medium.From the ANOVAs was evidenced that the treatments with better results were T7 EET-103 + Base petal + culture medium 1 T8 EET-103 + Base petal + Culture medium 2 T9 EET petal -103 + Base + culture medium 3, variable in which statistical significance was obtained. The floral explants from clone EET-103 was a suitable method for the development of embryogenesis, starting point for the regeneration of Theobroma cocoa.